Bacterial profile and antibiotic sensitivity in silk sutures following odontectomy - Endriani, Rita; Rafni, Elita; Prakoso, Agung; Prima, Wahyu; Hadi, Farhan; Alni, Azzahra Dwi; Dwideta, Vezi Adina (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Impacted teeth, hindered from erupting normally due to space constraints, obstruction by neighboring teeth, or an abnormal eruption pathway, often necessitate surgical intervention known as odontectomy. Silk sutures are commonly used in this procedure, yet they may serve as sites for bacterial colonization, potentially leading to infection. Following odontectomy, antibiotics are typically prescribed. Purpose: This study aims to identify the bacterial profile adhering to silk sutures and analyze antibiotic sensitivity patterns in patients undergoing odontectomy. Methods: A descriptive study employing consecutive sampling of patients after odontectomy was conducted between May and November 2021 at Arifin Achmad General Hospital, Riau Province, Indonesia. Sutures were removed within 14 days of surgery, after which the silk was identified and subjected to antibiotic sensitivity testing using the Kirby–Bauer method. Results: Of the bacteria detected in the silk sutures, 53.7% were Gram positive, including Streptococcus sp. (33.3%) and Staphylococcus aureus (13%), and 46.3% were Gram negative, such as Enterobacter sp. (20.4%) and Klebsiella sp. (16.7%). Among the multi-resistant strains, methicillin-resistant S. aureus (MRSA) accounted for 57.1%. The Gram-positive bacteria exhibited the highest sensitivity to levofloxacin, whereas the Gram-negative bacteria showed sensitivity to ceftazidime, levofloxacin, and meropenem. Conclusion: The most dominant Gram-positive bacteria were Streptococcus sp. and S. aureus, whereas the most dominant Gram-negative bacteria were Enterobacter sp. and Klebsiella sp. Levofloxacin, ceftazidime, and meropenem emerged as the most effective antibiotics following odontectomy. Multidrug-resistant bacteria, exemplified by MRSA, were identified within the oral cavity.